(untitled) (Research, Society and Development, 2022)
Introduction: Intensive Care Units (ICU) are environments intended for the care of critically ill patients, with potential risk of death, who need uninterrupted care. However, due to the population’s lack of knowledge about intensive care, hospitalization can be a situation of great stress, in which it generates long-term psychological problems after discharge from intensive care. Objective: to discuss long-term psychological outcomes after discharge from intensive care. Methodology: this is a descriptive narrative review of the literature. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and EBSCO Information Services. Results and discussion: among the most common psychological factors are depression, anxiety and post-traumatic stress disorder. Such factors are caused by the excessive use of sedatives and invasive procedures, as well as the prevalence of feelings of anguish and disability upon admission to the ICU, due to the erroneous idea of ​​the ICU as a “place of death”. Final considerations: the role of the Physician and Psychologist in monitoring the person under intensive care is essential, using active listening in order to clarify the patient’s doubts about the true concept of ICU. In addition, the intensive care physician must evaluate each patient in order to reduce invasive procedures and unnecessary sedation, in order to reduce long-term psychological problems after discharge from intensive care.